Discharge and structural characteristics of MgO thin films under various O2 and H2 gas flow rates during MgO deposition when using ion plating method in microdischarge cells. (4th March 2017) - Kim, Dong Ha; Park, Choon-Sang; Jung, Eun Young; Kim, Hyun-Jin; Seo, Heaseok; Hong, Jung Goo; Shin, Bhum Jae; Tae, Heung-Sik
ABSTRACT: This paper has investigated the characteristics of structure and discharge for the MgO thin films grown by the ion plating process by varying the oxygen (O2 ) and hydrogen (H2 ) flow rates. The structural characteristics of the MgO film are measured by scanning electron microscopy (SEM), X-ray diffraction (XRD), and atomic force microscopy (AFM). The discharge characteristics are examined based on the firing voltage, secondary electron emission, sustain delay, and address delay. By increasing the O2 flow rates during ion plating process, the grain sizes of the MgO thin films are decreased and the firing voltages are decreased, which would be due to the improvement of secondary electron emission characteristics. In addition, as the O2 gas flow rates are increased in the range from 200 to 260 sccm, the sustain delay times are reduced, on the contrary, the address delay times are increased. Whereas, by increasing the H2 flow rates, the grain sizes of the MgO thin films are increased. In particular, the lower firing voltages are measured at a H2 flow rate of 40 sccm, which also would be due to an enhancement of secondary electron emission characteristics. When H2 flow rates are increased from 0 to 40 sccm, the address delay times are greatly reduced. Whereas, when H2 flow rates are beyond 40 sccm, the address delay times are slightly increased. However, the sustain delay times are slightly increased as the H2 flow rates are increased from 0 to 60 sccm. Accordingly, the optimal control of both O2 and H2 flow rates during the MgO film deposition using ion plating method can contribute to enhancing the discharge characteristics in ac plasma display panels (ac-PDPs).